Language as a Tool of Struggle: A Sociopragmatic Analysis of Demand Statements in Police Reports on Demonstrations - Dr. Tri Santoso, M.Pd.; Dr. Hari Kusmanto, M.Pd. (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025, 2025)
Language in police reports on demonstrations often functions not merely as a neutral record of events but as a strategic device that conveys demands, frames social struggles, and legitimizes authority or resistance. The study employs a descriptive qualitative research method that includes the types of illocutionary acts and social functions of the 39 online news headlines as data. Data were gathered through documentation, observation, and note-taking and were analysed using methods of intralingual matching and pragmatic matching. Results show that the directive illocutionary acts, conveying explicit demands or commands, are dominant (87.18%), followed by expressive acts (7.69%) and assertives (5.13%). Outstanding social functions include investigation on corruption/illegality (48.72%), dismissal/job negotiating (17.95%), protection/rejotion of environment/project (7.69%) and other functions (e.g., demand for social justice, demand for lifting the life-level of the public, socialistic critique), ranging from 2.56% to 10.26%). In a global context, these issues are very easy to relate to both for anticorruption and environmental campaigns around the developing world who are fighting the same governance issues in their home countries. Interdisciplinarily, this research adds to the field of linguistics, sociology and communication studies to explain that on-line media language does not work purely as informative, airchanal language, but also it works like a strategic device of Indonesia civil movement in order to mobilize society, to stem up a civil advocacy, and influence on public policy in contemporary Indonesia. They reinforce language as a catalyst of social innovation under the democratizing navalieu of democracy and global justice.